ORAL DEPENDENCY: A POTENTIAL RISK FACTOR FOR GASTRIC LESIONS - Waqas Manzoor; Bukhtawar Naz; Ali Boricha; Shumaila Ismail; Muhammad Akbar; Humaira Zakir; Hina Khan (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Objective:To evaluate the correlation of oral addictions with the risk to develop the gastric lesions.Place & Duration of the study:The study was conducted at Isra University, Karachi and Hyderabad campus. From March 2024 to July 2025.Methodology:A cross sectional analytical study was done on 200 numbers of patients, both gender were included with any age range. The non-probability convenient sampling technique was adopted to enroll the patients after conformation of gastric lesion on gastroscopy and on the basis of history of the oral addiction and symptoms relatable. Patients with previous history of treatment and surgical intervention, any trauma and on chemotherapy were excluded. The finding were documented on proforma and data analyzed through SPSS. The qualitative data was presented in the form of Frequency and percentage, while the correlation was evaluated by applied Chi-square test. The P value was set at P=